2011
DOI: 10.1002/art.30419
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity is associated with magnetic resonance imaging–based knee cartilage T2 measurements in asymptomatic subjects with and those without osteoarthritis risk factors

Abstract: Objective To evaluate the association of exercise and knee-bending activities with magnetic resonance (MR)-based knee cartilage T2 relaxation times and morphologic abnormalities in asymptomatic subjects with and without osteoarthritis (OA) risk factors from the Osteoarthritis Initiative. Methods We studied 128 subjects with knee OA risk factors and 33 normal controls aged 45–55 years, with a body mass index of 18–27 kg/m2, and no knee pain. Subjects were categorized by exercise level, using the leisure activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 47 publications
2
63
1
2
Order By: Relevance
“…A U-shaped association between physical activity levels and cartilage lesions was suggested: intermediate activity levels were associated with the lowest T2 (ie, the healthiest cartilage), suggesting a protective impact of moderate activity 89 91. T2 also differed between subjects with OA risk factors and those without; T2 was associated with Body Mass Index (BMI)92 93 and greater BMI also was associated with greater incidence and progression of cartilage lesions 94.…”
Section: Imaging Publications From Full Cohort Releasesmentioning
confidence: 99%
See 1 more Smart Citation
“…A U-shaped association between physical activity levels and cartilage lesions was suggested: intermediate activity levels were associated with the lowest T2 (ie, the healthiest cartilage), suggesting a protective impact of moderate activity 89 91. T2 also differed between subjects with OA risk factors and those without; T2 was associated with Body Mass Index (BMI)92 93 and greater BMI also was associated with greater incidence and progression of cartilage lesions 94.…”
Section: Imaging Publications From Full Cohort Releasesmentioning
confidence: 99%
“…T2 also differed between subjects with OA risk factors and those without; T2 was associated with Body Mass Index (BMI)92 93 and greater BMI also was associated with greater incidence and progression of cartilage lesions 94. Further studies found trochlear dysplasia95 and ACL abnormalities associated with cartilage degenerative change 91. While T2 was found to have potential for monitoring early disease, it may be less useful in monitoring disease progression once cartilage defects have occurred 96…”
Section: Imaging Publications From Full Cohort Releasesmentioning
confidence: 99%
“…9e11 These early changes are quantifiable through T2 value mapping, and include increases in water content and alterations in the collagen content and architecture. 11,12 T2 values have been shown in different studies to be sensitive to cartilage alterations, as seen in OA 9,10,13,14 or after surgical cartilage repair procedures. 15,16 Because the use of T2 value measurements allows the detection of early biochemical shifts in the cartilage matrix prior to irreversible morphological changes, it is a technique that may be well suited to evaluate the effects of risk factors, such as ligament injury, on ankle cartilage health.…”
Section: Introductionmentioning
confidence: 99%
“…High T 2 values correlate with histological degeneration of cartilage, implying increased free water content and collagen disorientation (8,22). However, in subjects with high OA risk, light exercise has been associated with better cartilage quality (16).…”
mentioning
confidence: 99%